The impact of the assimilation of migrants on the well-being of native inhabitants: A theory - Oded Stark; Jakub Bielawski; Marcin Jakubek (University of Tübingen, Faculty of Economics and Social Sciences, 2014)
We present a theory that systematically and causally links the well-being of native inhabitants with variation in the extent of the assimilation of migrants. Recent empirical findings are yielded as predictions of the theory.
urn:nbn:de:bsz:21-dspace-584934
Keywords: I31; J61; 330; Migrants' assimilation; The well-being of native inhabitants